Understanding society : through spiritual-scientific knowledge : social three-folding, Christ, Lucifer and Ahriman : fifteen lectures given in Dornach between 3 October and 15 November 1919 /: through spiritual-scientific knowledge : social three-folding, Christ, Lucifer and Ahriman : fifteen lectures given in Dornach between 3 October and 15 November 1919. (2017) - Steiner, Rudolf, 1861-1925
No abstract available